2020
DOI: 10.21093/sajie.v2i2.2188
|View full text |Cite
|
Sign up to set email alerts
|

Upaya Meremediasi Konsep Fisika pada Materi Suhu dan Kalor

Abstract: Miskonsepsi adalah salah satu masalah dalam pembelajaran fisika. Miskonsepsi fisika terjadi pada materi suhu dan kalor. Penelitian ini bertujuan untuk memberikan review terkait upaya yang telah dilakukan beberapa peneliti untuk meremediasi miskonsepsi materi suhu dan kalor. Materi yang diremediasi adalah suhu dan kalor. Metode penelitian kualitatif artikel review pada remediasi konsep suhu dan kalor. Hasil dari penelitian ini adalah review miskonsepsi fisika dalam kompetensi dasar suhu dan pemuaian, kalor dala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 3 publications
0
2
0
3
Order By: Relevance
“…This shows that misconceptions are still a problem in science learning. As in the research conducted by (Sofianto & Irawati, 2020), it was also found that students had misconceptions about temperature and heat. Therefore, teaching science to students can be done with meaningful learning.…”
Section: Resultsmentioning
confidence: 77%
“…This shows that misconceptions are still a problem in science learning. As in the research conducted by (Sofianto & Irawati, 2020), it was also found that students had misconceptions about temperature and heat. Therefore, teaching science to students can be done with meaningful learning.…”
Section: Resultsmentioning
confidence: 77%
“…Research conducted by Rahmawati & Bakhtiar (2019) regarding science learning based on the integration of Science on the Subject of the Creation of the Universe and the Solar System, the results of this research reveals that learning science on the material of the creation of the universe and the solar system is related to Islamic studies where this related to akhlak values to Allah SWT (Rahmawati & Bakhtiar, 2019). The subject of discussion regarding temperature has also been carried out by research, which states that the subject of temperature is related to the akhlak values listed in the Al-Quran (Sofianto & Irawati, 2020). Therefore, considering the results of previous research, it is essential to explore how science learning can be used to internalize akhlak values so that the religious character of students can also be formed.…”
Section: Introductionmentioning
confidence: 81%
“…Dalam penelitian ini ditemukan adanya miskonsepi pada sub topik Asaz Black yang cukup besar yakni sebanyak 46 (56,10%) mahasiswa. Azas Black merupakan salah satu bahasan yang sering membuat siswa mengalami miskonsepsi (Nurhasanah, Silitonga, & Oktavianty, 2016;Sofianto & Irawati, 2020;Utari & Liliawati, 2019;Wulandari, Prihandono, & Maryani, 2018). Miskonsepsi yang terjadi pada mahasiswa adalah ketika mereka dihadapkan dengan persoalan pencampuran kedua benda yang mana dalam pencapaian kesetimbangan termal terjadi perubahan wujud.…”
Section: Azas Balckunclassified